SEJARAH PERKEMBANGAN INDUSTRI KERAJINAN TENUN MELAYU SIAK (Studi Kasus Pada Usaha Tenun Wan Fitri Pekanbaru) - Resti, Pertiwi; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: Melayu weaving is one of the cultural products of the Melayu community in Riau. One of the famous Melayu weaving in Riau is the Melayu Siak weaving. In Pekanbaru city there are several handicraft industries of Melayu Siak woven, one of them is woven Melayu Wan Fitri handicraft industry. The purpose of this study is to (1) Know the background of the founding of Malay Woven Weaving industry Wan Fitri. (2) Knowing the development of Wan Fitri Malay Woven industry in 1969-2017. (3) Knowing the driving factors affecting the development of Wan Fitri Woven industry. (4) To know the constraints experienced in developing Wan Fitri Weaving industry. (5) Knowing how to face obstacles in developing Wan Wan Woven industry. The research method that writer use is qualitative method and by using data collecting technique like library study, observation, interview and documentation. Malay Woven Handicraft Industry Wan Fitri Pekanbaru is a weaving business owned by Mursidah founded in 1969. Wan Fitri Malay weaving business is experiencing development, this can be seen from the type of looms, labor and products produced. The tool used is gedogan loom and non-machine loom (ATBM). At the beginning of the business Murisidah did not have manpower, but now there are 42 workers. The main product types produced are woven fabrics, other than that there are other products such as wedding dress, clothes and embroidered embroidery.Keyword: History, Development, Siak Malay Weaving, Wan Fitri Weaving.